Patidar exports private limited - Varma, Poornima, (SAGE Knowledge. Cases., 2017)
In 2016, Vishant Patel, the founder of Patidar Exports Private Limited (PEPL), an export firm for cotton and other products in Ahmedabad, was planning to export to more countries. Patidar Exports already sold cotton to China, Bangladesh, Pakistan and Vietnam and Vishant now how to decide between Indonesia, Turkey and Thailand as the next market for his cotton. However, each market had its peculiarities. In Turkey there were many opportunities, but the entry regulations were stringent, whereas in Thailand the regulations were relaxed, but the competition was fierce. The students are given the relevant data about Turkey, Thailand and Indonesia cotton imports and invited to consider which of three countries is the best market for Vishant's cotton.